Enhanced activity and durability of novel activated carbon-supported PdSn heat-treated cathode catalyst for polymer electrolyte fuel cells. (20th February 2016) - Salomé, S.; Ferraria, A.M.; Botelho do Rego, A.M.; Alcaide, F.; Savadogo, O.; Rego, R.
Abstract: Novel carbon-supported PdSn electrocatalysts for ORR in PEFCs were synthesized by NaBH4 reduction method with and without carbon activation pre-treatment (i.e., Sn sensitization and Pd activation) followed by heat treatment at 300 °C in a H2 /N2 mixture and compared with Pd. The catalysts were characterized by EDX, XRD, TEM/SAED and XPS. The electrocatalytic activity for ORR was tested in acid medium using cyclic voltammetry, rotating disc electrode and chronoamperometry. For the first time, these catalysts were tested in a single H2 /O2 PEM fuel cell. Rotating disc electrode studies indicated that the new catalysts PdSn-3H and PdSn-2H exhibited, respectively, 10 and 4 times higher ORR activity than Pd catalyst, as well as higher methanol and ethanol tolerance. ORR proceeded through a 4-electron reduction pathway on both heat-treated catalysts. The new catalysts also exhibited improved electrochemical durability under potential cycling (600 cycles from −0.2 to 1.0 V) and constant potential (-0.55 V, 40 h). The observed high activity and durability of these catalysts may be attributed to: i) their specific alloying composition at their surface; ii) the graphitization degree of the carbon support and/or, iii) the presence of intermetallic compounds. H2 /O2 single fuel cell based on PdSn-2H cathode operating at 60 °C exhibited the highest ORR mass activity (1.36 A mgPd −1  at 0.6 V) among the previous results obtained in the literature on PdSnPt, Pd-based and Pd catalysts.